Impact of continuous glucose monitoring on everyday life of young children with type 1 diabetes and their parents: An evaluation of 114 families - Aouchiche, K.; Bernoux, D.; Baechler Sadoul, E.; Haine, E.; Joubert, F.; Epstein, S.; Faure Galon, N.; Dalla-Vale, F.; Combe, J.C.; Samper, M.; Simonin, G.; Castets, S.; et al. (Primary care diabetes, 2024)
The prevalence of type 1 diabetes is increasing worldwide. The advent of new monitoring devices has enabled tighter glycemic control. To study the impact of glucose monitoring devices on the everyday life of young children with type 1 diabetes (T1D) and their parents. A questionnaire was addressed to parents of children with T1D under the age of 6 years with an insulin pump treated in one of the hospitals of the ADIM network in France between January and July 2020. Among the 114 families included in the study, 53% of parents (26/49) woke up every night to monitor blood glucose levels when their child had flash glucose monitoring (FGM), compared with 23% (13/56) of those whose child had continuous glucose monitoring (CGM). Overall, 81% of parents (86/108) found that glucose monitoring improved their own sleep and parents whose child had CGM were significantly more likely to report improved sleep (86% vs 73%, p = 0.006). Forty-nine percent of parents (55/113) declared that they (in 87% of cases, the mother only) had reduced their working hours or stopped working following their child’s T1D diagnosis. Maternal unemployment was significantly associated with the presence of siblings (p = 0.001) but not with glycemic control (p = 0,87). Ninety-eight percent of parents (105/107) think that glucose monitoring improves school integration. In these families of children with T1D, new diabetes technologies reduced the burden of care but sleep disruption remained common. Social needs evaluation, particularly of mothers, is important at initial diagnosis of T1D in children. •Half of the parents reduced their working hours following their child’s diagnosis of diabetes.•Glucose sensors improved the sleep of the caregivers of young children with diabetes.•School integration was reported as improved by glucose sensors by most of the parents.